Male and Female Circumcision Medical, Legal, and Ethical Considerations in Pediatric Practice - Denniston, George C.; Hodges, Frederick Mansfield.; Milos, Marilyn Fayre. (Springer US, 1999)
Every year around the world 13.3 million boys and 2 million girls have part or all of their external sex organs cut off. Doctors, parents, and politicians have been misled into thinking that these mutilations are beneficial, necessary and harmless. International respected experts in the fields of medicine, science, politics, law, ethics, sociology, anthropology, history and religion present the latest research, documentation and analysis of this world-wide problem, focusing on the ethical, political and legal aspects of sexual mutilation; the cost and burden to healthcare systems; the latest medical research; anatomical and function consequences; religious and cultural aspects; psychological aspects; and the world-wide campaign to end sexual mutilation.